2003
DOI: 10.1046/j.1365-2958.2003.03712.x
|View full text |Cite|
|
Sign up to set email alerts
|

Disruption of mptpB impairs the ability of Mycobacterium tuberculosis to survive in guinea pigs

Abstract: SummaryProtein tyrosine kinases and tyrosine phosphatases from several bacterial pathogens have been shown to act as virulence factors by modulating the phosphorylation and dephosphorylation of host proteins. The identification and characterization of two tyrosine phosphatases namely MptpA and MptpB from Mycobacterium tuberculosis has been reported earlier.MptpB is secreted by M. tuberculosis into extracellular mileu and exhibits a pH optimum of 5.6, similar to the pH of the lysosomal compartment of the cell. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(149 citation statements)
references
References 38 publications
(47 reference statements)
5
141
0
Order By: Relevance
“…Unfortunately, how Mtb evades the host immune responses remains unknown. Given the observation that Mtb-lacking mPTPB are unable to survive in macrophages and in guinea pig (11), it has been hypothesized that mPTPB may promote mycobacterial survival in the host by targeting the IFN-γ mediated signaling pathway, although the exact mechanism by which this occurs has not been elucidated. Since mPTPB functions within the macrophage, we established Raw264.7 mouse macrophage cell lines stably expressing mPTPB in order to investigate the role of mPTPB in host cell biology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, how Mtb evades the host immune responses remains unknown. Given the observation that Mtb-lacking mPTPB are unable to survive in macrophages and in guinea pig (11), it has been hypothesized that mPTPB may promote mycobacterial survival in the host by targeting the IFN-γ mediated signaling pathway, although the exact mechanism by which this occurs has not been elucidated. Since mPTPB functions within the macrophage, we established Raw264.7 mouse macrophage cell lines stably expressing mPTPB in order to investigate the role of mPTPB in host cell biology.…”
Section: Resultsmentioning
confidence: 99%
“…Given the absence of endogenous tyrosine phosphorylation within Mtb, mPTPA and mPTPB likely modify macrophage proteins to manipulate host-pathogen interactions. Interestingly, genetic deletion of mPTPB blocks intracellular survival of Mtb in interferon-γ (IFN-γ) activated macrophages and severely reduces the bacterial load in a clinically relevant guinea pig model of TB infection (11). These findings led to the hypothesis that mPTPB might mediate mycobacterial survival in macrophages by targeting host cell processes, although the underlying molecular basis is not understood.…”
mentioning
confidence: 99%
“…It uses its own PtdInsmannoside to inhibit PtdIns3P production (256) but also secretes a phosphatase, called SapM capable of dephosphorylating PtdIns3P (1630). Another phosphatase, MptpB, which is an important virulence factor of Mycobacterium tuberculosis (1411), is a trifunctional enzyme that hydrolyzes phosphoserine/threonines, phosphotyrosines, and phosphoinositides (120,121). While inhibiting PtdIns3P production of the host, Mycobacteria also synthesize PtdIns3P (1085), apparently as an intermediate of PtdIns synthesis and not as a result of PtdIns phosphorylation (1084).…”
Section: B Infectious Diseasesmentioning
confidence: 99%
“…In this experiment, it was found that the disruption of mPTPB gene resulted in 70-fold reduction in the bacterial load in the spleen of guinea pigs. Complementary strain, obtained after reintroducing the gene into the mutant strain, regained the ability to infect the guinea pigs at rates comparable to the parent strain [8]. Beresford et al also studied the growth of mycobacteria in resting macrophages in order to mimic the infection in a susceptible host (where IFNγ activation may be impaired).…”
Section: Introductionmentioning
confidence: 99%